1997
DOI: 10.1542/peds.100.4.e3
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Dexamethasone Therapy for the Prevention of Chronic Lung Disease in Preterm Infants With Respiratory Distress Syndrome: A Multicenter Clinical Trial

Abstract: ABSTRACT. Objectives. To study whether early postnatal (<12 hours) dexamethasone therapy reduces the incidence of chronic lung disease in preterm infants with respiratory distress syndrome.Materials and Methods. A multicenter randomized, double-blind clinical trial was undertaken on 262 (saline placebo, 130; dexamethasone, 132) preterm infants (<2000 g) who had respiratory distress syndrome and required mechanical ventilation shortly after birth. The sample size was calculated based on the 50% reduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 36 publications
7
137
0
6
Order By: Relevance
“…From these data some individuals suggested that the prevalence of SIP was so small that additional trials of early postnatal steroids were warranted for risk versus benefit analyses. 38 For the purpose of this paper, the NNH was calculated comparing all studies to date that used an a priori definition, 33,39 -43 versus those without, 32,[34][35][36][37][44][45][46] to illustrate the disturbing impact of this reporting bias ( Figure 2). With an a priori definition, for every 16 infants receiving postnatal steroids, one developed SIP.…”
Section: The History Of Spontaneous Intestinal Perforationmentioning
confidence: 99%
“…From these data some individuals suggested that the prevalence of SIP was so small that additional trials of early postnatal steroids were warranted for risk versus benefit analyses. 38 For the purpose of this paper, the NNH was calculated comparing all studies to date that used an a priori definition, 33,39 -43 versus those without, 32,[34][35][36][37][44][45][46] to illustrate the disturbing impact of this reporting bias ( Figure 2). With an a priori definition, for every 16 infants receiving postnatal steroids, one developed SIP.…”
Section: The History Of Spontaneous Intestinal Perforationmentioning
confidence: 99%
“…1,9,10 However, there is no evidence demonstrating a direct cause-effect relationship. The lack of an accepted severity of illness score for newborns after the first 24 h of life 11 complicates interpretation of the data, as glucose instability can be an expression of severity of illness, 12,13 which may be the risk factor for ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids (GC) are widely used in immature newborns because of their anti-inflammatory effects (7). Increasing evidence indicates that GC administration in early life may have long-term effects, including growth retardation (8), cardiac dilatation, and cardiac hypertrophy (9).…”
mentioning
confidence: 99%